1999
DOI: 10.4102/sajbm.v30i1.749
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and organisational effectiveness in the administration of cricket in South Africa

Abstract: After years of isolation from the international sporting arena, South African sports teams have recently achieved much success. This article is concerned specifically with managing for organisational effectiveness in South African cricket. According to the theory of transformational leadership, there should be a positive relationship between this style of leadership and organisational effectiveness. The Multifactor Leadership Questionnaire was used to collect information about leadership while data for organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
2
15
1
Order By: Relevance
“…Based on relevant literature already examined, a substantial relationship was likely to exist between worker performance as well as an emotional intelligent, transformational leader, however this research doesn't confirmed the expectation. The findings of the research did not offer the conclusions attracted by authors for example (17), and (18), which claim that worker performance is going to be characterized by high amounts of transformational leadership minimizing amounts of transactional leadership. Furthermore, the outcomes of the foremost and second ideas don't concur using the literature and former research presented, as research by (15), (19), (20)and (21) indicate an optimistic relationship between leadership and worker performance and an optimistic relationship between leadership and emotional intelligence.…”
Section: Discussioncontrasting
confidence: 87%
“…Based on relevant literature already examined, a substantial relationship was likely to exist between worker performance as well as an emotional intelligent, transformational leader, however this research doesn't confirmed the expectation. The findings of the research did not offer the conclusions attracted by authors for example (17), and (18), which claim that worker performance is going to be characterized by high amounts of transformational leadership minimizing amounts of transactional leadership. Furthermore, the outcomes of the foremost and second ideas don't concur using the literature and former research presented, as research by (15), (19), (20)and (21) indicate an optimistic relationship between leadership and worker performance and an optimistic relationship between leadership and emotional intelligence.…”
Section: Discussioncontrasting
confidence: 87%
“…The effectiveness of a group of people depends heavily on leadership qualities. Effective leader behavior can facilitate the achievement of follower desires, which can improve performance [35] [36]. [37] suggest that effective leadership styles will inspire and motivate employees to work hard to achieve the goals and successes of individuals and organizations.…”
Section: Leadership Style and Employee Performancementioning
confidence: 99%
“…It has been shown that the followers have more interest in transformational leadership rather than transactional leadership (Druskat, & Kayes, 2000). Transformational leadership and organizational effectiveness have significant relationship in the South Africa cricket administration (Ristow et al, 1999). Some researchers also found that work withdrawal and transformational leadership has negative relationship (Gill et al, 2010).…”
Section: Transformational Leadership and Employee's Job Satisfactionmentioning
confidence: 99%